QUANTIFICATION OF PRIMARY METABOLITES OF MORINGA OLEIFERA LAM - ARCHANA SHARMA,; ANITA YADAV,; NACHIKETA BARMAN,; MANVI MALWAL, (The Bioscan, 2010)
Since time immemorial, man has used various plant parts in the treatment and prevention of various ailments. These plants provide biologically active metabolites and lead structures whose activities can be enhanced by manipulation through combinations with chemicals and synthetic chemistry. These metabolites can be exploited in the field of new drugs research and for the development of modified derivatives with enhanced activity and reduced toxicity. In the present investigation, various plant parts (leaves, stems, roots and pods) of Moringa oleifera was evaluated for their biochemical estimation of primary metabolites viz., total soluble sugar, starch, phenol, protein and lipid. The plant parts varied in composition of their primary metabolites. Results showed that the maximum content of soluble sugar (57.2±0.53 mg/gdw) and phenols (41.0±0.33 mg/gdw) were found in stem part, starch (42.0±0.60 mg/gdw) and lipid (46.0±0.05 mg/gdw) in leaf part and proteins in pods (41.0±0.30 mg/gdw) of M.oleifera. It further concludes that Moringa oleifera plant parts are rich source of primary metabolites and can be used as raw material in industries.